2004
DOI: 10.1177/076737010401900301
|View full text |Cite
|
Sign up to set email alerts
|

Comprendre et mesurer la valeur du point de vue du consommateur

Abstract: Cet article propose une intégration des travaux sur la valeur de consommation et un cadre conceptuel reposant sur la théorie fonctionnelle des attitudes dans lequel nous identifions six composantes de la valeur de consommation (utilitaire, connaissance, stimulation expérientielle, lien social, expression de soi, spirituelle). Par ailleurs, nous proposons un modèle intégrateur expliquant la valeur globale (ratio entre bénéfices et sacrifices) par les composantes de la valeur de consommation. Une application au … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1
95

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(190 citation statements)
references
References 30 publications
2
89
1
95
Order By: Relevance
“…The existence of statistically equivalent models can be considered as a limitation in the present case since, as can be seen from the literature review, the direction of the relationship between perceived value and satisfaction is still a controversial topic in the marketing literature (e.g. Aurier et al, 2004, Cronin et al, 2000.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of statistically equivalent models can be considered as a limitation in the present case since, as can be seen from the literature review, the direction of the relationship between perceived value and satisfaction is still a controversial topic in the marketing literature (e.g. Aurier et al, 2004, Cronin et al, 2000.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…The first one stipulates that global value and satisfaction can act in parallel (Oliver, 1996(Oliver, , 1999Cronin et al, 2000). For Aurier et al (2004), this approach can only be valid within the framework of repeated experiences with the service, so that value and satisfaction can be considered in a cumulative view. The second one considers value as a consequence of satisfaction (Cronin et al, 2000).…”
Section: The Mediating Role Of Valuementioning
confidence: 99%
“…The sign and stimulation dimensions were clearly remaining, although the items of the social-link component and the information-search dimension defi ned the third dimension. Aurier et al 35 found a strong correlation between these two dimensions. In the context of this study, it seems as if speaking with other participant consumers about sport practice refers to both a will to share and a desire to improve knowledge.…”
Section: Consumer-value Segmentationmentioning
confidence: 99%
“…Aurier et al 35 identifi ed two types of consumer value. The fi rst focuses on a service ' s global value from an exchange perspective, whereas the second focuses on consumption value, which addresses the fi eld of consumption or possession experiences.…”
Section: -34mentioning
confidence: 99%
See 1 more Smart Citation